(untitled) (Jurnal Luminous: Riset Ilmiah Pendidikan Fisika, 2025)
Technological developments cannot be avoided in this 21st century. The development of technology is evenly distributed and increasingly prevalent in every field of life, including in the field of education. In 21st century education, technology has become the main complement in every learning activity. 21st century learning focuses on student-centered learning which aims to improve four learning competencies, namely critical thinking, collaboration, communication, and creative thinking (4C Skills). One of the abilities expected in the 21st century is critical thinking. This study aims to analyze the need for the development of teaching materials in the form of E-LKPD based on Problem Based Learning (PBL) to improve students’ critical thinking skills in Particle Dynamics material. The study used a qualitative descriptive method with the Hannafin & Peck Research and Development (R&D) model approach at the needs analysis stage. The subjects of the study were 50 high school students at SMAN 1 Guguak District who were selected using random sampling techniques. The instruments used included questionnaires, interviews, and critical thinking tests. The results showed that students’ critical thinking skills were still low, with an average score of 45.96%, especially on the Basic Support indicator. In addition, teachers still predominantly use conventional models and teaching materials that do not support the development of critical thinking. Meanwhile, the majority of students prefer digital-based and problem-based learning. This finding indicates the need for the development of PBL-based E-LKPD as a solution to improve the quality of physics learning and students’ critical thinking skills in the digital era.